Functional and Psychosocial Characteristics of Elderly in Federation of Bosnia and Herzegovina (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
The aim of the research was to identify psychosocial factors and functional characteristics of the elderly. The survey covered a stratified sample of 60 patients with advanced age, both sexes, living in a family environment. In order to assess functional and psychosocial characteristics of older persons were used: Barthel index test, self-assessment scale for depression, self-esteem Rosenberg scale, PD Questionnaire / Form A scale for assessing the degree of social support, as well as Structured questionnaire of personal data which we collected data on gender, age, marital status, number of children, diagnosis, and self-economic situation. Data analysis was performed using parametric and nonparametric statistics. To determine the latent space of applied variables factor analysis was used. Based on the results of the study there are four (4) factors: Factor of somatopsychic dimensions of existential anxiety, Factor of socioeconomic status, Factor of social status and Health status factor.